Une Révolution tranquille : l’évolution de l’image du père dans la dramaturgie québécoise - Jakubczuk, Renata (Romanica Silesiana)
In spite of the implications of its name, the Quiet Revolution in Quebec seems to be rather tempestuous at the family level. The conflict between generations, set in a historic context, puts into question the functioning of the entire society, especially the dominant role of the father. The objective of this article, therefore, is to analyze the position of the father in the social context. Thus, I discuss various types of fathers: a farmer father, the patriarch who leaves the household chores to the wife; a worker father, subservient to both his wife at home and to his boss at the factory; a bourgeois father who works for himself; and finally, an immigrant father who seeks his place within the new society.